2018
DOI: 10.1037/ppm0000133
|View full text |Cite
|
Sign up to set email alerts
|

“Like” me: Shopping, self-display, body image, and social networking sites.

Abstract: Ideals of beauty and product information are transmitted via sociocultural channels, including social media. Through the framework of objectification theory, we examined the relation of involvement on Facebook to women's internalization of appearance ideals, psychological well-being, and their intentions to make online purchases. Participants were 796 female college students who completed online measures regarding internalization, sources of beauty information, social comparisons, body satisfaction, self-estee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 78 publications
1
22
0
1
Order By: Relevance
“…Quantitative studies primarily recruited participants from university cohorts (n = 23), of which three were psychology cohorts with the majority based in the USA, followed by Australia . Three studies recruited participants in community settings (n = 3) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative studies primarily recruited participants from university cohorts (n = 23), of which three were psychology cohorts with the majority based in the USA, followed by Australia . Three studies recruited participants in community settings (n = 3) .…”
Section: Resultsmentioning
confidence: 99%
“…Study sample size ranged from 100 to 1104 participants with a mean age of 18.5 to 25.78 years, of which 84% were female. Where ethnicity was reported in studies (n = 23), participants were mostly Caucasian . Of the 12 studies that reported BMI, participants had a mean range between 20.26 and 28.24 kg/m 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of the analyzed studies directly test for social comparison (Greitemeyer, 2016;Hanna et al, 2017;Kang, Chung, Mora, & Chung, 2013;Liu et al, 2017;Stapleton, Luiz, & Chatwin, 2017;Vogel, Rose, Okdie, Eckles, & Franz, 2015;Vogel et al, 2014;Wang, Wang, Gaskin, & Hawk, 2017;Yang, Holden, & Carter, 2018). The results of another four studies can be interpreted in the light of social comparison theory (Chen et al, 2016;Gonzales & Hancock, 2011;Strubel, Petrie, & Pookulangara, 2018;Wang, Yang, & Haigh, 2017). Table 3 presents these findings.…”
Section: Social Comparison Processes On Snssmentioning
confidence: 95%
“…Passive SNS use, characterized by browsing other peoples' profiles without active interaction or participation, is closely linked to social comparisons (Krasnova et al, 2015). Users who frequently engage in passive SNS use, like viewing selfies of others, report lower levels of self-esteem (Chen et al, 2016;Strubel et al, 2018;R. Wang et al, 2017).…”
Section: Social Comparison Processes On Snssmentioning
confidence: 99%